Numerical study of fluid flow and heat transfer enhancement of nanofluids over tube bank - Wahid, M. A. (2013)
In the present work, laminar cross flow forced convective heat transfer of nanofluid over tube banks with various geometry under constant wall temperature condition is investigated numerically. We used nanofluid instead of pure fluid ,as external cross flow, because of its potential to increase heat transfer of system. The effect of the nanofluid on the compact heat exchanger performance was studied and compared to that of a conventional fluid.The two-dimensional steady state Navier-Stokes equations and the energy equation governing laminar incompressible flow are solved using a Finite volume method for the case of flow across an in-line bundle of tube banks as commercial compact heat exchanger. The nanofluid used was alumina-water 4% and the performance was compared with water. In this paper, the effect of parameters such as various tube shapes ( flat, circle, elliptic), and heat transfer comparison between nanofluid and pure fluid is studied. Temperature profile, heat transfer coefficient and pressure profile were obtained from the simulations and the performance was discussed in terms of heat transfer rate and performance index. Results indicated enhanced performance in the use of a nanofluid, and slight penalty in pressure drop. The increase in Reynolds number caused an increase in the heat transfer rate and a decrease in the overall bulk temperature of the cold fluid. The results show that, for a given heat duty, a mas flow rate required of the nanofluid is lower than that of water causing lower pressure drop. Consequently, smaller equipment and less pumping power are required.